Answer:
A. There is one solution. The solution set is {(1, -2, -3)}
Step-by-step explanation:
We have the system:
![$$\left\{ \begin{array}{llI} 2x-6y+4z=2&\\ x+2y-z=0 & \\6x-y-z=11 & \quad \end{array} \right.$$](https://tex.z-dn.net/?f=%24%24%5Cleft%5C%7B%20%20%20%20%20%20%20%20%5Cbegin%7Barray%7D%7BllI%7D%20%20%20%20%20%20%20%20%20%20%20%202x-6y%2B4z%3D2%26%5C%5C%20%20%20%20%20%20%20%20%20%20%20%20x%2B2y-z%3D0%20%26%20%5C%5C6x-y-z%3D11%20%26%20%5Cquad%20%20%20%20%20%20%20%20%20%5Cend%7Barray%7D%20%20%20%20%5Cright.%24%24)
Let's try to solve this system.
There's no single method to approach a system like this. We simply have to think about it and then do a guess and check approach.
Anyways, we can try to figure out one of our variables first. Let's try to figure out x. To do so, we can use substitution. From the second equation, let's add z to both sides. This yields:
![x+2y=z](https://tex.z-dn.net/?f=x%2B2y%3Dz)
Now, substitute this to the third equation:
![6x-y-(x+2y)=11](https://tex.z-dn.net/?f=6x-y-%28x%2B2y%29%3D11)
Distribute:
![6x-y-x-2y=11](https://tex.z-dn.net/?f=6x-y-x-2y%3D11)
Subtract:
![5x-3y=11](https://tex.z-dn.net/?f=5x-3y%3D11)
Let's solve for y. Add 3y to both sides and subtract 11 from both sides:
![3y=5x-11](https://tex.z-dn.net/?f=3y%3D5x-11)
Divide everything by 3:
![y=\frac{5}{3}x-\frac{11}{3}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B5%7D%7B3%7Dx-%5Cfrac%7B11%7D%7B3%7D)
Now, we go back to the first equation:
![2x-6y+4z=2](https://tex.z-dn.net/?f=2x-6y%2B4z%3D2)
Substitute what we know for y and z:
![2x-6(\frac{5}{3}x-\frac{11}{3})+4(x+2y)=2](https://tex.z-dn.net/?f=2x-6%28%5Cfrac%7B5%7D%7B3%7Dx-%5Cfrac%7B11%7D%7B3%7D%29%2B4%28x%2B2y%29%3D2)
Distribute:
![2x-10x+22+4x+8y=2](https://tex.z-dn.net/?f=2x-10x%2B22%2B4x%2B8y%3D2)
Now, let's substitute y. This will leave only the x-variable remaining. So:
![2x-10x+22+4x+8(\frac{5}{3}x-\frac{11}{3})=2](https://tex.z-dn.net/?f=2x-10x%2B22%2B4x%2B8%28%5Cfrac%7B5%7D%7B3%7Dx-%5Cfrac%7B11%7D%7B3%7D%29%3D2)
Let's simplify. Combine like terms:
![-4x+22+8(\frac{5}{3}x-\frac{11}{3})=2](https://tex.z-dn.net/?f=-4x%2B22%2B8%28%5Cfrac%7B5%7D%7B3%7Dx-%5Cfrac%7B11%7D%7B3%7D%29%3D2)
Distribute:
![-4x+22+\frac{40}{3}x-\frac{88}{3}=2](https://tex.z-dn.net/?f=-4x%2B22%2B%5Cfrac%7B40%7D%7B3%7Dx-%5Cfrac%7B88%7D%7B3%7D%3D2)
Remove the fractions by multiplying everything by 3:
![-12x+66+40x-88=6](https://tex.z-dn.net/?f=-12x%2B66%2B40x-88%3D6)
Combine like terms:
![28x-22=6](https://tex.z-dn.net/?f=28x-22%3D6)
Add 22 to both sides:
![28x=28](https://tex.z-dn.net/?f=28x%3D28)
Divide both sides by 28. So, the value of x is:
![x=1](https://tex.z-dn.net/?f=x%3D1)
Now, we can use the other equation to determine our other variables.
Go back to the following equation we acquired:
![y=\frac{5}{3}x-\frac{11}{3}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B5%7D%7B3%7Dx-%5Cfrac%7B11%7D%7B3%7D)
Substitute 1 for x:
![y=\frac{5}{3}-\frac{11}{3}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B5%7D%7B3%7D-%5Cfrac%7B11%7D%7B3%7D)
Subtract:
![y=-\frac{6}{3}=-2](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B6%7D%7B3%7D%3D-2)
So, the value of y is -2.
And to find z, we can use the following equation we acquired at the beginning:
![z=x+2y](https://tex.z-dn.net/?f=z%3Dx%2B2y)
Substitute 1 for x and -2 for y. So:
![z=(1)+2(-2)](https://tex.z-dn.net/?f=z%3D%281%29%2B2%28-2%29)
Multiply:
![z=1-4](https://tex.z-dn.net/?f=z%3D1-4)
Subtract:
![z=-3](https://tex.z-dn.net/?f=z%3D-3)
So, our answer is A. There is one solution, which is (1, -2, -3).
And we're done!